2021
DOI: 10.1016/j.heliyon.2021.e06418
|View full text |Cite
|
Sign up to set email alerts
|

The effect of direct and extended contact on attitudes towards social robots

Abstract: The development of social robots has the potential to address significant societal concerns, however, most people have limited experience of such technology. The present research investigated whether techniques borrowed from the psychology of intergroup relations – namely direct and extended contact – affect people's attitudes towards robots. Participants were provided with either direct contact with a social robot or extended contact (these participants watched a video recorded by a friend who had met the rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…This assumption is also strengthened by recent research based on intergroup relations. Sarda Gou et al, 2021 ) showed that direct contact with robots positively affected participants’ explicit and implicit attitudes toward robots. Direct contact might also be the crucial factor in why we found rather reserved attributions to robots while people working with robots attribute positive and negative human characteristics to them ( Sauppé & Mutlu, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption is also strengthened by recent research based on intergroup relations. Sarda Gou et al, 2021 ) showed that direct contact with robots positively affected participants’ explicit and implicit attitudes toward robots. Direct contact might also be the crucial factor in why we found rather reserved attributions to robots while people working with robots attribute positive and negative human characteristics to them ( Sauppé & Mutlu, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The IAT appears to be an essential method to reduce measurement error by assessing superior psychometric evaluations in direct comparisons with explicit measures. This study would suggest, respectively or simultaneously, using several data sources that cover different types of IATs: (a) the Single-Target Implicit Association Test (ST-IAT) that highlights a single dimension of target concepts (i.e., no contrasting concept to service robot), (b) the Multi-Dimensional Implicit Association Test (MD-IAT) that generates the index of reaction times in multidimensional concept dynamics (e.g., Gattol et al, 2011), or (c) the newly developed IAT that includes developed lists of words and pictures as stimuli with regard to service robots (Gou et al, 2021). These approaches might result in a better understanding of the complexities of gender differences in implicit attitudes toward robots.…”
Section: Methodological Implicationsmentioning
confidence: 99%
“…This study aims to introduce an application of the IAT to tap into implicit attitudes toward robotic services and show that such concepts and approaches can inform research about the emerging trends of robotic technologies in hospitality services. The essence of such endeavors stems from the empirical studies underlying the association between implicit measures of attitudes and explicit measures of robot attitudes (Gou et al, 2021), as well as from the structuring principle that a high proportion of individuals' decision making takes place beyond conscious awareness (Maison et al, 2004). Nonetheless, insufficient attention has been paid to the concept of implicit attitude in empirical research on the adoption of service robots in human cognitive behavior.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Therefore, it is inevitable to understand user perceptions, corresponding attributions, and evoked feelings, especially when it comes to the acceptance of users of bionic devices and social robots on a broader societal level. Notwithstanding, we must consider that nowadays, the majority of people have no direct contact with such devices, and their attitudes towards them might be formed based on fiction rather than fact (Sarda Gou et al 2021). Accordingly, we aim at a deeper understanding of how the basic principles of social perception influence the formation of attitudes towards social robots and bionics users and whether or how social perception is influenced in turn by different grades of technicity.…”
Section: Introductionmentioning
confidence: 99%